1998
DOI: 10.1002/malq.19980440305
|View full text |Cite
|
Sign up to set email alerts
|

Undecidability of the Real‐Algebraic Structure of Scott's Model

Abstract: We show that true first-order arithmetic of the positive integers is interpretable over the real-algebraic structure of Scott's topological model for intuitionistic analysis. From this the undecidability of the structure follows. Mathematics Subject Classification: 03D45, 03F55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For the encoding of sets of natural numbers we shall generalize the following construction used in Scott's model in [3]. Let N+ denote the set of positive natural numbers.…”
Section: Outline Of the Proof Of Theorem 11mentioning
confidence: 99%
See 1 more Smart Citation
“…For the encoding of sets of natural numbers we shall generalize the following construction used in Scott's model in [3]. Let N+ denote the set of positive natural numbers.…”
Section: Outline Of the Proof Of Theorem 11mentioning
confidence: 99%
“…There were results by Smoryński (in [15]) and by Cherlin (in [1]) suggesting that this might be the case. Indeed, building on Cherlin's work, in [3] we were able to interpret true first order arithmetic in the L ‐theory of Scott's model. Then, in [4] we extended this result to the classes of models defined by Scowcroft [13, 14] and Krol [7].…”
Section: Introductionmentioning
confidence: 99%
“…Let L denote the language of ordered rings. In [5], using a coding similar to the one used by Cherlin in [1], we showed that the L-theory of Scott's topological model for intuitionistic analysis is undecidable by encoding true first-order arithmetic in that structure. (Scott defined the model in question in [9].)…”
Section: An Application: Interpretation Of Intuitionistic Second Orde...mentioning
confidence: 99%